The high-affinity human IgG receptor Fc gamma receptor I (FcγRI) is not associated with vascular leakage of dengue - Zamberi, Z.M.; Zakaria, Z.; Aziz, A.T.A.; Heng, B.S.L.; Zaid, M.; Chong, C.L.K.; Noor, F.M.; AbuBakar, Sazaly; Peng, H.B. (BioMed Central, 2015)
Background: Dengue is a major public health problem in many tropical and sub-tropical countries. Vascular leakage and shock are identified as the major causes of deaths in patients with severe dengue. Studies have suggested the potential role of Fc gamma receptors I (FcγRI) in the pathogenesis of dengue. We hypothesized that the circulating level of Fcγ receptor I could potentially be used as an indicator in assisting early diagnosis of severe dengue. Results: A selected cohort of 66 dengue patients including 42 dengue with signs of vascular leakage, and 24 dengue without signs of vascular leakage were identified and were afterwards referred to as 'cases' and 'controls' respectively. Thirty seven normal healthy controls were also recruited in this study. The circulating level of FcγRI was quantified from the serum using enzyme-link immunosorbent assay (ELISA). The levels of FcγRI in both groups of patients with and without vascular leakage were found to be significantly higher than the normal healthy controls (P < 0.001). However, there was no significant difference found between patients with vascular leakage and those without vascular leakage (p = 0.777). Conclusion: We suggest that FcγRI is not associated with the vascular leakage in dengue. However, further studies are necessary to delineate the role of FcγRI in antibody-dependent enhancement (ADE) mechanism.